2018
DOI: 10.1159/000488170
|View full text |Cite
|
Sign up to set email alerts
|

LPS Pretreatment Attenuates Cerebral Ischaemia/Reperfusion Injury by Inhibiting Inflammation and Apoptosis

Abstract: Background/Aims: Lipopolysaccharide (LPS) pretreatment has a strong neuroprotective effect on cerebral ischaemia/reperfusion injury (IRI), but the mechanism has not been fully elucidated to date. This study investigated the effect of LPS pretreatment on the pathway mediated by endoplasmic reticulum (ER) stress–CCAAT/enhancer-binding protein- homologous protein (CHOP) and the role of this pathway on cerebral ischaemia/reperfusion (I/R)-induced inflammation and apoptosis. Methods: Healthy male BALB/c mice were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The UPR is attributed to the activation of one ER transmembrane protein, named protein kinase RNA-like ER kinase (PERK) (15)(16)(17). Growing evidence has shown that ERS associated with apoptosis and inflammation plays important roles in IR injury (18,19). UPR could gradually develop into apoptosis and further induces inflammation, if ERS is too severe to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…The UPR is attributed to the activation of one ER transmembrane protein, named protein kinase RNA-like ER kinase (PERK) (15)(16)(17). Growing evidence has shown that ERS associated with apoptosis and inflammation plays important roles in IR injury (18,19). UPR could gradually develop into apoptosis and further induces inflammation, if ERS is too severe to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Many I/R animal models showed neuronal apoptosis [ 4 ], which is also evident in patients suffering from ischemic stroke [ 5 ]. Cerebral I/R induces the activation of a series of pro-apoptotic genes or inactivation of anti-apoptotic genes, leading to neuronal cell damage [ 6 , 7 ]. Therefore, searching for protective agents directed at apoptotic pathways may provide an attractive therapeutic approach for the therapy of cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that caSR-induced ca 2+ release from internal stores is a PLc-mediated/IP3-dependent process. The enhancement of [ca 2+ ]i may be related to the release of ca 2+ by the ER (6,26). To examine the occurrence of ER stress, the protein levels of GRP78 were detected.…”
Section: Discussionmentioning
confidence: 99%